Neoadjuvant chemotherapy increases the 5-year overall survival of patients with resectable cervical cancer: A systematic review and meta-analysis - Yunbao Xu; Mengting Zhang; Jiaying Zhang; Derry Minyao Ng; Xiaoxiao Chen; Yuexiu Si; Yetan Shi; Xiangyuan Li; Danyi Mao; Lu Yang (Elsevier, 2021)
Cervical cancer is a global health challenge in women. Neoadjuvant chemotherapy (NACT) is a recent prospect for alternative cervical cancer treatments. This study investigated the efficacy of NACT against resectable cervical cancer based on the medium and long-term survival of patients with the disease. We searched through PubMed, Web of Science, EBSCO and Cochrane Library for relevant reports published by June 2020. The primary outcomes were 3-year and 5-year progression-free survival (PFS) and overall survival (OS) of patients with resectable cervical cancer. Overall, 22 publications encompassing 5627 patients fulfilled the inclusion criteria. We found NACT not to affect both 3-year PFS and OS as well as 5-year PFS of patients with resectable cervical cancer. However, NACT significantly improves the 5-year OS of patients with resectable cervical cancer (HR = 0.83, 95% CI: 0.73-0.94, p = 0.013). Subgroup analysis (RCTs, non-RCTs, NACT + surgery + AT vs. surgery + AT, NACT + surgery + AT vs. CCRT/RT/CRT) further revealed NACT had no significant effect on 5-year PFS of patients with resectable cervical cancer, converse to the 5-year OS subgroup analysis, which validated the beneficial effect of NACT in patients with resectable cervical cancer. In addition, the effect of NACT was most significant in the non-RCTs subgroup (p = 0.012). NACT may improve the long-term prognosis of patients with resectable cervical cancer. However, further large-scale multicenter studies are needed to validate this finding.